2021
DOI: 10.1016/j.afjem.2021.07.002
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence, management, and thirty-day outcomes of symptomatic atrial fibrillation in a Tanzanian emergency department

Abstract: Introduction Data describing atrial fibrillation (AF) care in emergency centres (ECs) in sub-Saharan Africa is lacking. We sought to describe the prevalence and outcomes of AF in a Tanzanian EC. Methods In a prospective, observational study, adults presenting with chest pain or shortness of breath to a Tanzanian EC were enrolled from January through October 2019. Participants underwent electrocardiogram testing which were reviewed by two independent physician judges to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…This study was a secondary analysis of data collected during two prospective surveillance studies of chest pain in the KCMC ED, with detailed methods reported elsewhere 18,19,29–31 . Enrollment procedures for the two studies were identical.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study was a secondary analysis of data collected during two prospective surveillance studies of chest pain in the KCMC ED, with detailed methods reported elsewhere 18,19,29–31 . Enrollment procedures for the two studies were identical.…”
Section: Methodsmentioning
confidence: 99%
“…This study was a secondary analysis of data collected during two prospective surveillance studies of chest pain in the KCMC ED, with detailed methods reported elsewhere. 18,19,[29][30][31] pain or shortness of breath, as identified by patient-reported chief complaint at presentation. Chest pain secondary to trauma, selfreported fever, or inability to provide informed consent were considered exclusion criteria.…”
Section: Selection Of Participantsmentioning
confidence: 99%